A NEW SEISMIC MODEL OF THE MOON: IMPLICATIONS FOR STRUCTURE, THERMAL EVOLUTION AND FORMATION OF THE MOON - Lognonné P.; Gagnepain-Beyneix J.; Chenet H. (My University, 2003)
The seismic determinations of the crustal thickness and mantle velocities are key parameters for most geophysical and geochemical lunar studies. We determine a new seismic model of the Moon after a complete independent reprocessing of the Apollo lunar seismic data with determination of arrival times of about 60 natural and artificial lunar quakes, as well as travel times of converted phases at the crust–mantle interface below the Apollo 12 landing site. On the near side in the Procellarum KREEP Terrane, the only major discontinuity compatible with the crust–mantle boundary is located around 30 km deep. In this terrane, seismic constraints on the crust and mantle lead to a 30 km thick anorthositic crust and a pyroxenite cold mantle, with a bulk composition of 6.4% Al2O3, 4.9% CaO and 13.3% FeO. Mantle temperatures are in accordance with profiles obtained from the observed electrical conductivity and exclude a liquid Fe core, while being compatible with a Fe–S liquid core. Our Moon model might be explained by a mixture of a primitive Earth with tholeiitic crust and depleted upper mantle, together with a chondritic enstatitic parent body for the impactor planet. It provides mixture coefficients comparable to those obtained by impact simulation as well as an estimate of bulk U of about 28 ppb, in accordance with the U budget in a 40 km mean thick crust, 700 km thick depleted mantle and a lower undepleted primitive mantle.